2011
DOI: 10.1007/s10620-011-1577-2
|View full text |Cite
|
Sign up to set email alerts
|

Getting to the Core of the Women’s Curriculum—It’s Time to Change the Way We Train Our Fellows

Abstract: In the United States, 50.7 percent of the population are women [1]. In 2004 there were an estimated 104 million visits for evaluation and management of a digestive disease, and after adjustment for age the number of visits was 10 percent higher for women than for men, which equates to over 57 million visits per year for women [2]. Although many digestive diseases are the same in men and women, there are also many differences. Research has shown that there are gender differences in epidemiology, response to hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Some subspecialties, such as Gastroenterology, have attempted to integrate women's health/SRH into required training milestones for fellows. However, as these milestones often do not require a demonstration of competency, it is understandable why a national sample of gastroenterology fellows reported that they had received inadequate SRH training during fellowship and did not feel competent to provide SRH to patients 47–49 …”
Section: Subspecialists Require Training and Continuing Medical Educa...mentioning
confidence: 99%
See 2 more Smart Citations
“…Some subspecialties, such as Gastroenterology, have attempted to integrate women's health/SRH into required training milestones for fellows. However, as these milestones often do not require a demonstration of competency, it is understandable why a national sample of gastroenterology fellows reported that they had received inadequate SRH training during fellowship and did not feel competent to provide SRH to patients 47–49 …”
Section: Subspecialists Require Training and Continuing Medical Educa...mentioning
confidence: 99%
“…Develop national curricula on SRH and widely disseminate them (e.g., through the American Association of Medical College's MedEdPortal), particularly for training programs that lack local expertise. 48,51 Develop local SRH curricula, done by faculty leaders from ObGyn/MFM and/or experts in subspecialty medicine with expertise in SRH.…”
Section: Subspecialists Require Training and Continuing Medical Educa...mentioning
confidence: 99%
See 1 more Smart Citation